Pengaruh Risiko Bisnis, Ukuran Perusahaan, Pertumbuhan Aset, Profitabilitas dan Penghematan Pajak Terhadap Struktur Modal pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Pratania Putri, Arie; Sintauli Nababan, Veronika; Ratna Sari Simbolon, Desi (CV. Publikasi Indonesia, 2022)
Tax savings are efforts made by company management to obtain profits based on the use of debt. Efforts to save taxes from the application of debt can lead to a high value of a company because the capital structure obtained comes from the use of debt. This study aims to examine whether the Capital Structure of IDX Food and Beverage Companies 2018-2020 can be influenced by Tax Savings, Profitability, Asset Growth, Company Size, and Business Risk in the implementation of this research. This research is a type of research in the form of quantitative research. There are 26 companies as the research population, where purposive sampling technique is used by researchers to select study samples. Meanwhile, there are 78 perceptions as the number of research observations. Capital structure can have a simultaneous effect on business risk, capital structure will have a simultaneous positive effect on firm size, and capital structure will have a simultaneous positive effect on asset growth. capital structure has a simultaneous negative effect on profitability, and capital structure has a simultaneous positive effect on tax savings.